A dominant-negative transgene defines a role for p56lck in thymopoiesis. - Levin, S D (1993)
The lymphocyte-specific protein tyrosine kinase p56lck participates in T cell signaling through functional interactions with components of the T cell antigen receptor complex and the interleukin-2 receptor. Additional insight into the function of p56lck has now been obtained through the generation of transgenic animals expressing high levels of a catalytically inactive form of this kinase (p56lckR273). Mice bearing the lckR273 transgene manifested a severe defect in the production of virtually all T lymphocytes. Those exceptional CD3+ cells that escaped the effects of the lckR273 transgene were confined primarily to the T cell subset that expresses gamma/delta T cell receptors. Remarkably, construction of a dose-response curve for the effects of the lckR273 transgene revealed that developmental arrest of thymocytes occurred at a discrete stage in the normal T cell maturation pathway, corresponding to a point at which thymoblasts ordinarily begin a series of mitotic divisions that result in expansion and maturation. These results suggest that p56lck normally regulates T cell production by metering the replicative potential of immature thymoblasts.